2016
DOI: 10.1111/pbr.12431
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epistatic and environmental interaction QTLs for leaf orientation‐related traits in maize

Abstract: Leaf architecture traits in maize are quantitative and have been studied by quantitative trait loci (QTLs) mapping. However, additional QTLs for these traits require mapping and the interactions between mapped QTLs require studying because of the complicated genetic nature of these traits. To detect common QTLs and to find new ones, we investigated the maize traits of leaf angle, leaf flagging‐point length, leaf length and leaf orientation value using a set of recombinant inbred line populations and single nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…In maize, statistical epistasis is rarely observed in QTL analyses (Edwards et al ., ; Stuber et al ., ; Briggs et al ., ) or in genome‐wide scans in panels of inbred maize lines (Wallace et al ., ) – but see Shi et al . () for epistatic effects in leaf orientation – but is more commonly found when individual cloned QTLs are placed into otherwise isogenic maize or teosinte backgrounds (Doebley et al ., ; Weber et al ., ; Studer & Doebley, ). As variation both in the genotype and phenotype of a causative locus must occur in a mapping population, studies focusing on maize specifically may fail to observe differences.…”
Section: Genetic Interactions and Selection During Maize Domesticationmentioning
confidence: 99%
“…In maize, statistical epistasis is rarely observed in QTL analyses (Edwards et al ., ; Stuber et al ., ; Briggs et al ., ) or in genome‐wide scans in panels of inbred maize lines (Wallace et al ., ) – but see Shi et al . () for epistatic effects in leaf orientation – but is more commonly found when individual cloned QTLs are placed into otherwise isogenic maize or teosinte backgrounds (Doebley et al ., ; Weber et al ., ; Studer & Doebley, ). As variation both in the genotype and phenotype of a causative locus must occur in a mapping population, studies focusing on maize specifically may fail to observe differences.…”
Section: Genetic Interactions and Selection During Maize Domesticationmentioning
confidence: 99%
“…Based on a published review (Cao et al, 2022), the QTL information have been reported for LA-related traits (Lu et al, Frontiers in Genetics frontiersin.org 03 Duan et al 10.3389/fgene.2022.1004211 2007; Ku et al, 2010;Tian et al, 2011;Ku et al, 2012;Chen et al, 2015;Ding et al, 2015;Li et al, 2015;Ku et al, 2016;Pan et al, 2017;Shi et al, 2017;Wang et al, 2017;Dzievit et al, 2019;Liu et al, 2019;Zhang et al, 2019;Tang et al, 2021). The QTL information (Chromosome, LOD, R 2 , Confidence Interval and so on) were summarized from eighteen studies published in the lasted 15 years.…”
Section: Meta-analysesmentioning
confidence: 99%
“…Oryza sativa TGA2 (OsTGA2) can directly regulate defenserelated genes (Moon et al, 2018). The key points in the regulation of sunflower resistance by TGA may be involved in the resistance of sunflower to Verticillium dahliae (Guo et al, 2017). In addition, ROXY can be used as TGA-dependent promoter to control the negative regulators of detoxification genes in A. thaliana (Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a published review (Cao et al, 2022), the QTL information have been reported for LA-related traits (Lu et al, 2007;Ku et al, 2010;Tian et al, 2011;Ku et al, 2012;Chen et al, 2015;Ding et al, 2015;Hu et al, 2015;Li et al, 2015;Yang et al, 2015;Ku et al, 2016;Pan et al, 2017;Shi et al, 2017;Wang et al, 2017;Dzievit et al, 2019;Liu et al, 2019;Zhang et al, 2019;Zhang et al, 2020;Tang et al, 2021). The QTL information (Chromosome, LOD, R 2 , Confidence Interval and so on) were summarized from eighteen studies published in the lasted 15 years.…”
Section: Meta-analysesmentioning
confidence: 99%